'I feel like I can do it now': preservice teacher efficacy in a co-teaching community of practice. Issue 1 (2nd January 2019) - Hawkman, Andrea M.; Chval, Kathryn B.; Kingsley, Laurie H.
Abstract: Teacher efficacy, or teachers' feelings about their abilities in the classroom, remains a major component of educational research. We know that despite participating in shared or similar experiences, some preservice teachers (PSTs) develop feelings of teacher efficacy and some do not. Yet, in-depth examinations into the specific practices of successful host schools are scarce in the deep field of teacher efficacy research. We examine the deliberate actions of one Midwestern elementary school to establish a climate and co-teaching process that deliberately seeks to foster PST success and feelings of confidence in the classroom. We also discuss implications for teacher education.